Process intensification approach for design and optimization of biodiesel production from palm fatty acid distillate - Im-orb, Karittha; Arpornwichanop, Amornchai; Simasatitkul, Lida (My University, 2021)
Design of the biodiesel production from palm fatty acid distillate (PFAD) using process intensification approach is studied in technical, economic and environmental view points. Firstly, the transport phenomena analysis is performed to select the suitable intensified unit. The reactive distillation is selected and used in esterification – transesterification process and hydrolysis – esterification process. The optimum condition of reactive distillation in esterification – transesterification is achieved when the methanol is fed at the 3rd stage of the 4-stage column and the liquid holdup is maintained at 6 m3. The intensified esterification – transesterification process offers higher biodiesel yield and consumes less energy compared with the intensified hydrolysis – esterification process. The economic analysis shows that the intensified esterification-transesterification process is found to be economically feasible. Finally, environment assessment based on life cycle analysis (LCA) indicates that the environmental impact of both processes are similar.
Keywords: Biodiesel production; Economic analysis and environmental analysis; Palm fatty acid distillate; Process design; Process intensification